Dynamiques contemporaines. - Goormans, Claude; Jamart, Christine; Joiret, Marie-Hélène; Meuris, Jacques; Neuray, Marie-Claire (Paris : Centre Wallonie-Bruxelles, 1991)
Bogart, Bram ; Broodthaers, Marcel ; Corillon, Patrick ; Fauville, Daniel ; François, Michel ; Frère, Michel ; Garcet, Robert ; Mouffe, Michel ; Octave, Jean-François ; Queeckers, Bernard ; Rocour, Lambert ; Xiao Xia
biog. [1 p.] per kunstenaar
Frans
Dynamiques contemporaines, Centre Wallonie-Bruxelles, Paris, 28 septembre au 9 novembre 1991
boek